2013
DOI: 10.1093/cvr/cvt206
|View full text |Cite
|
Sign up to set email alerts
|

The galectin-3/RAGE dyad modulates vascular osteogenesis in atherosclerosis

Abstract: These data indicate a novel molecular mechanism by which galectin-3 and RAGE modulate in divergent ways, not only inflammation, but also vascular osteogenesis, by modulating Wnt/β-catenin signalling, and independently of ALEs/AGEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 35 publications
7
79
0
3
Order By: Relevance
“…This finding indicates that galectin-3 contributes to the promotion of macrophage activation and monocyte attraction in atherosclerotic plaque destabilization [19]. A recent study pointed out that galectin-3 modulates vascular calcification, which is associated with inflammation and plaque instability [20]. Previous studies showed that galectin-3 plays a role not only in atherosclerotic plaque activation but also in the development of atherosclerosis [21,22].…”
Section: Discussionmentioning
confidence: 96%
“…This finding indicates that galectin-3 contributes to the promotion of macrophage activation and monocyte attraction in atherosclerotic plaque destabilization [19]. A recent study pointed out that galectin-3 modulates vascular calcification, which is associated with inflammation and plaque instability [20]. Previous studies showed that galectin-3 plays a role not only in atherosclerotic plaque activation but also in the development of atherosclerosis [21,22].…”
Section: Discussionmentioning
confidence: 96%
“…Wnt signaling promotes VSMC survival,20 whereas silencing Wnt signaling reduces cell proliferation 21. Along with cellular proliferation, some data suggested that Wnt signaling may play a role in the VSMC migration during intimal thickening,2, 22 motility,23 and osteogenesis 24. Moreover, a recent study has demonstrated a role for Wnt5a in cholesterol efflux by VSMCs 25…”
Section: Components Of the Vasculature Systemmentioning
confidence: 99%
“…RAGE відіграють важливу роль у патогенезі атеросклерозу і розвитку супу-тньої патологічної мінералізації. Відмічено, що їх експресія ко-локалізується з фокусами запа-лення у нестабільних атеросклеротичних бляш-ках з мікрокальцифікацією [45]. На додаток, ви-явлена сумісна локалізація і підвищена експресія RAGE з судинними ГМК, які підлягають остео-хондрогенній диференціації [46].…”
Section: фактор росту фібробластів 23 (Fgf23) Klotho та хронічна нирunclassified
“…Початкове відкладення депозитів кальцію відбу-вається у відповідь на прозапальні стимули у вигляді точкового або гранулярного відкладення сполук кальцію. Такий паттерн відомий як «мік-рокальцифікація», він також характеризується індукцією запалення за типом «хибного кола» [45,54]. Така форма патологічної біомінераліза-ції у атеросклеротичній бляшці може сприяти її розриву.…”
Section: фактор росту фібробластів 23 (Fgf23) Klotho та хронічна нирunclassified